The impact of monitoring and sanctioning on unemployment exit and job-finding rates - Duncan McVicar (IZA World of Labor, 2014)
Unemployment benefits often reduce incentives to search for a job. Policymakers have responded to this behaviour by setting minimum job search requirements, by monitoring to check that unemployment benefit recipients are engaged in the appropriate level of job search activity, and by imposing sanctions for infractions. Empirical studies consistently show that job search monitoring and benefit sanctions reduce unemployment duration and increase job entry in the short term. There is some evidence that longer-term effects of benefit sanctions may be negative.
Keywords: I38; J65; J68; 330; unemployment; job search; sanctions; monitoring